Cytoplasmic kinases downstream of GPR30 suppress gonadotropin-releasing hormone (GnRH)-induced luteinizing hormone secretion from bovine anterior pituitary cells - RUDOLF, Faidiban O.; KADOKAWA, Hiroya (Journal of Reproduction and Development, 2016)
GPR30 is known as a membrane receptor for picomolar concentrations of estradiol. The GPR30-specific agonist G1 causes a rapid, non-genomic suppression of gonadotropin-releasing hormone (GnRH)-induced luteinizing hormone (LH) secretion from bovine anterior pituitary (AP) cells. A few studies have recently clarified that protein kinase A (PKA) and phosphorylated extracellular signal-regulated kinase (pERK) might be involved in cytoplasmic signaling pathways of GPR30 in other cells. Therefore, we tested the hypothesis that PKA and ERK kinase (MEK) are important cytoplasmic mediators for GPR30-associated non-genomic suppression of GnRH-induced LH secretion from bovine AP cells. Bovine AP cells (n = 8) were cultured for 3 days under steroid-free conditions. The AP cells were previously treated for 30 min with one of the following: 5000 nM of PKA inhibitor (H89), 1000 nM of MEK inhibitor (U0126), or a combination of H89 and U0126. Next, the AP cells were treated with 0.01 nM estradiol for 5 min before GnRH stimulation. Estradiol treatment without inhibitor pretreatment significantly suppressed GnRH-induced LH secretion (P < 0.01). In contrast, estradiol treatment after pretreatment with H89, U0126 or their combination had no suppressive effect on GnRH-induced LH secretion. The inhibitors also inhibited the G1 suppression of GnRH-induced LH secretion. Therefore, these data supported the hypothesis that PKA and MEK (thus, also pERK) are the intracellular mediators downstream of GPR30 that induce the non-genomic suppression of GnRH-induced LH secretion from bovine AP cells by estradiol or G1.